164k views
2 votes
Benjamin solved the following equation: 4x − 2x + 8 = 6(x + 4) Step Work Justification 1 4x − 2x + 8 = 6x + 24 Combine like terms 2 2x + 8 = 6x + 24 Combine like terms 3 −4x + 8 = 24 Subtraction property of equality 4 −4x = 16 Subtraction property of equality 5 x = −4 Division property of equality Which step has an incorrect justification?

User Aduric
by
5.0k points

1 Answer

7 votes
For this case we have the following expression:
4x - 2x + 8 = 6 (x + 4)
The first step is:
4x - 2x + 8 = 6x + 24
The first step is, correct.
However, the justification "Combine like terms" is NOT correct.
The correct justification is:
Distributive property of multiplication.
Answer:
A step that has an incorrect justification is:
Step 1
User Linyaa
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.